2017
DOI: 10.21834/e-bpj.v2i5.691
|View full text |Cite
|
Sign up to set email alerts
|

A Qualitative Study on the Determination of Healthy Cafeteria Practice in Selangor, Malaysia

Abstract: The prevalence of obesity around the world is increasing yearly. Dietary intake, physical inactivity, and sedentary lifestyle are the common causes of obesity. This situation has created an urge to improve a healthy eating environment in the community. Eating outside is more common nowadays especially during working hours. Workers normally will have their meal at the cafeteria. Their dietary intake is directly affected by the availability of food choices at the cafeteria. Thus, a qualitative study was conducte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 48 publications
1
1
0
Order By: Relevance
“…Conversely, some previous studies documented high levels of good food safety practices in FSE, such as restaurants, cafeterias, and stationary street food vendors [38,21,44]. However, in conformity with our findings, a number of earlier studies showed comparable degrees of poor hygiene practices among food handlers [45]. This inconsistency in food safety practice level might due to differences in the study tools used, geographical area, and sociodemographic characteristics.…”
Section: Food Safety Practices Of Food Handlerssupporting
confidence: 80%
“…Conversely, some previous studies documented high levels of good food safety practices in FSE, such as restaurants, cafeterias, and stationary street food vendors [38,21,44]. However, in conformity with our findings, a number of earlier studies showed comparable degrees of poor hygiene practices among food handlers [45]. This inconsistency in food safety practice level might due to differences in the study tools used, geographical area, and sociodemographic characteristics.…”
Section: Food Safety Practices Of Food Handlerssupporting
confidence: 80%
“…This implies that students who showed good food safety knowledge levels exhibit relatively better food safety practices. Since students enrolled in science departments showed better food safety knowledge than their colleagues in non-science departments, they may show better food safety practices because they may have an understanding of the consequences of not practising food safety This assertion is supported by Lambiri et al (2016) and Salhadi et al (2017).…”
Section: -89mentioning
confidence: 91%